Immunogenicity of AHSV-4 VP7 crystals and their potential use as a vaccine delivery platform - Bailey, Laura Victoria (2016)
African horse sickness (AHS) is a devastating disease of many equids and in the absence of effective treatment, vaccination plays an important role. Concerns of the commercially available live attenuated vaccine have stimulated the development of novel recombinant vaccines. The viral protein VP7 of AHSV induces high levels of antibody in infected horses. Both viral replication, and expressed VP7 in insect cells, results in the generation of hexagonal crystalline structures composed entirely of VP7 (~5pm in diameter). The aim of this thesis was to explore the immunogenicity of VP7 crystals and their potential as a novel vaccine delivery platform.